Are the reduction and oxidation properties of nitrocompounds dissolved in water different from those produced when adsorbed on a silica surface? A DFT M05‐2X computational study. Issue 14 (3rd March 2015) - Sviatenko, Liudmyla K.; Isayev, Olexandr; Gorb, Leonid; Hill, Frances C.; Leszczynska, Danuta; Leszczynski, Jerzy
Abstract : The reduction and oxidation properties of four nitrocompounds (trinitrotoluene [TNT], 2, 4‐dinitrotoluene, 2, 4‐dinitroanisole, and 5‐nitro‐2, 4‐dihydro‐3 H ‐1, 2, 4‐triazol‐3‐one [NTO]) dissolved in water as compared with the same properties for compounds adsorbed on a silica surface were studied. To consider the influence of adsorption, cluster models were developed at the M05/tzvp level. A hydroxylated silica (001) surface was chosen to represent a key component of soil. The PCM(Pauling) and SMD solvation models were used to model water bulk influence. The following properties were analyzed: electron affinity, ionization potential, reduction Gibbs free energy, oxidation Gibbs free energy, and reduction and oxidation potentials. It was found that adsorption and solvation decrease gas phase electron affinity, ionization potential, and Gibbs free energy of reduction and oxidation, and thus, promote redox transformation of nitrocompounds. However, in case of solvation, the changes are more significant than for adsorption. This means that nitrocompounds dissolved in water are easier to transform by reduction or oxidation than adsorbed ones. Among the considered compounds, TNT was found to be the most reactive in an electron attachment process and the least reactive for an electron detachment transformation. During ionization, a deprotonation of adsorbed NTO was found to occur. © 2015 Wiley Periodicals, Inc. Abstract : Reduction and oxidation properties of trinitrotoluene (TNT), 2, 4‐dinitrotoluene (DNT), 2, 4‐dinitroanisole (DNAN), and 5‐nitro‐2, 4‐dihydro‐3 H ‐1, 2, 4‐triazol‐3‐one (NTO) were studied in gas phase, in water, and adsorbed on a silica surface state. It was found that adsorption and solvation promote redox transformation of nitrocompounds. Nitrocompounds dissolved in water are easier to transform than adsorbed ones. Reactivity in an electron attachment and electron detachment processes increases in the rows: DNT < DNAN ≈ NTO < TNT and TNT < DNT < DNAN < NTO, respectively.